"InstantSocial" – Implementing a Distributed Mobile Multi-user Application with Adaptation Middleware - Fraga, Luís; Hallsteinsen, Svein; Scholz, Ulrich (Electronic Communications of the EASST, 2008)
In this position paper we explore how new capabilites of mobile devices could be used to setup distributed multi-user mobile applications with potentially high interest for end users. We describe an example of such an application by transposing Internet social network trends and principles to a mobile ad hoc environment. Then we present a tentative design and implentation sketch of this application in terms of the MUSIC context-aware adaptation middleware we are currently developing.